Preparation method of porous PTFE (Polytetrafluoroethylene) filled composite membrane
By coupling the functionalization treatment of ethanol and dopamine to the PTFE porous membrane and filling it with high sulfonation degree SPEEK75 and low sulfonation degree SPAES45 copolymer, the water loss and poor stability of the existing fuel cell proton exchange membrane at high temperatures are solved. problem, a porous PTFE-filled composite membrane with high proton conductivity and stability was achieved.
Patent Information
- Application Number
- CN202411514137.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-21
AI Technical Summary
The existing fuel cell proton exchange membranes have severe water loss at high temperatures, high cost, and severe fuel penetration. The hydrocarbon-based polymer membranes have poor stability under oxidation conditions, which limits their practical application.
The preparation method of porous PTFE filled composite membrane is adopted, and the hydrophilicity of the base membrane is improved by the coupling function of ethanol and dopamine on PTFE multi -porous membranes, and high sulfidalized Speek75 and low sulfurization are filled in its pores. SPAES45 convergence.
Multi -porous PTFE filling film with high quality and stability has been realized. The surface is smooth and dense, the conductivity is high, and the stability is good. It is suitable for the fields of fuel cells, membrane separation and ion exchange resin.
Smart Images

Figure CN119340404A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cell proton exchange membranes, and in particular relates to a method for preparing a porous PTFE-filled composite membrane. Background Art
[0002] Fuel cells have attracted wide attention for their high efficiency, environmental friendliness, and low pollutant emissions, and are considered to be a promising new clean energy conversion device. Proton exchange membrane (PEM) is a key component of fuel cells, and its performance directly determines the performance and service life of fuel cells. Classic perfluorosulfonic acid membranes such as Nafion ® Series of membranes, the disadvantages of severe water loss at high temperature, high cost, and severe fuel permeation are still difficult to overcome. An important alternative approach is to design a new generation of PEMs, especially based on hydrocarbon polymers, such as sulfonated polyarylethersulfone (SPAES), sulfonated polyetheretherketone (SPEEK), sulfonated polyetherketonesulfone (SPEKS), etc. This type of membrane has excellent film-forming properties, excellent processing properties and good thermochemical stability. Hydrocarbon polymer membranes can effectively improve their proton conductivity by increasing the ion exchange capacity (IEC), but at the same time, excessive sulfonic acid groups will cause excessive expansion or mechanical strength degradation, as well as poor stability under oxidative conditions, which seriously limits their practical application. To this end, researchers have adopted a variety of different modification methods to improve the comprehensive performance of the membrane, including doping, blending, cross-linking and other methods.
[0003] The filled composite membrane is a new type of PEM formed by filling a polymer electrolyte into a porous base membrane. Compared with the original hydrocarbon polymer membrane, the filled composite membrane exhibits the advantages of small swelling rate, high proton conductivity and low cost. At present, using porous membranes such as polytetrafluoroethylene (PTFE) with better stability and higher mechanical strength as the base membrane, filling the pores with proton-conducting polymer electrolytes is one of the effective means to improve the proton conductivity and stability of the membrane. Patent document CN 114464854 B is a method for preparing a composite filled electrolyte membrane, which uses a PTFE microporous membrane as a base membrane, and the PTFE microporous membrane gives the filled membrane good mechanical properties, 73% high sulfonation degree polyetheretherketone or 50% sulfonation degree polyarylethersulfone provides high conductivity; 40% low sulfonation degree polyarylethersulfone ensures the stability of the membrane; multiple impregnations and 40% low sulfonation degree polyarylethersulfone coating ensure the density and low fuel permeability of the membrane. However, the filling composite membrane prepared by this method is relatively cumbersome, and the filling effect is unstable, and the obtained proton conductivity is low (only 30~75 mS / cm). The literature (Journal of Membrane Science694 (2024) 122431) proposed a simple ethanol treatment of the PTFE-based membrane and then filling the membrane with a blend of SPEEK70 and SPAES40. This method improved the stability and proton conductivity of the membrane to a certain extent. However, due to the low hydrophilicity of the PTFE-based membrane surface and the low polymer filling efficiency, the proton conductivity of the membrane was not significantly improved. Summary of the invention
[0004] The purpose of the present invention is to design a method for preparing a porous PTFE-filled composite membrane with high proton conductivity and stability, so as to prepare a porous-filled composite membrane with better comprehensive performance.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a porous PTFE-filled composite membrane, characterized in that: the method is as follows: Step (1): Functionalization of PTFE porous substrate: The PTFE porous membrane is immersed in an ethanol solution for ultrasonic cleaning, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; dopamine hydrochloride and Tris solution are used to prepare a dopamine aqueous solution, the PTFE porous membrane is taken out from the ethanol solution and immersed in the above dopamine aqueous solution, and then taken out after standing in a dark environment, repeatedly rinsed with deionized water, and then dried for use; Step (2): Preparation of two-component filled polymer: A certain amount of SPEEK75 and SPAES45 were weighed and dissolved in the DMAc solution, and stirred with a magnetic stirrer to allow the polymer to be fully dissolved, and mixed solutions with different mass volume ratios were prepared; Step (3): Preparation of two-component filled composite membrane: The PTFE membrane is always kept in an ethanol-wetted state, and the two-component mixed solution prepared in step (2) is poured onto the PTFE microporous membrane, and evenly coated with a film scraper, and then heated in a film casting oven to form a film; finally, the filled composite membrane is immersed in a 1 mol / L HCl solution for 48 h to convert it into a proton form, and then rinsed with deionized water, and naturally dried to obtain a porous PTFE-filled composite membrane.
[0006] Furthermore, in step (1), the ultrasonic cleaning is performed for more than 0.5 h, the pH of the Tris solution is 8.5, the standing time in a dark environment is 10 to 18 h, and the concentration of the dopamine aqueous solution is 1.0 to 2.0 mg / mL.
[0007] Furthermore, the product in step (1) is placed in a 60° C. oven and dried for 3 h for later use.
[0008] Furthermore, in step (2), the stirring time of the magnetic stirrer is 24 h, and the mass volume ratio of the two-component polymer to the DMAc solution is 8% to 12%.
[0009] Furthermore, in step (3), the mass ratio of SPEEK75 to SPAES45 in the two-component mixed solution is 0.5-2.0.
[0010] Furthermore, in step (3), the conditions for heating the film in the film casting oven are: staying at 60°C for 4 to 6 hours, staying at 80°C for 8 to 10 hours, and staying at 100°C for 2 to 4 hours.
[0011] The following beneficial effects can be obtained through the above technical solution: The present invention uses a commercial PTFE porous membrane as a base membrane and uses an "ethanol + polydopamine" coupling process to functionally modify it, which can effectively improve the hydrophilicity of the base membrane and is conducive to the efficient filling of the polymer electrolyte in the later stage; The filling polymer adopts a copolymer of SPEEK75 with a high degree of sulfonation and SPAES45 with a low degree of sulfonation. By adjusting different proportions, the proton conductivity and stability of the filling membrane can be improved at the same time, meeting the application requirements of related fields, especially fuel cells, membrane separation, ion exchange resins and other fields. The preparation process of the invention is simple, and the obtained composite membrane has good filling effect, a smooth and dense surface, and has the advantages of high conductivity, good stability and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1(A1) and (A2) are SEM surface images and cross-sectional images of the base membrane PTFE; Figure 1 (B1) and (B2) are the SEM surface images and cross-sectional images of the filled membrane PD@PTFE / SPE-SPA (1:1).
[0013] Figure 2 Infrared spectra of PTFE, SPEEK75, SPAES45 and PD@PTFE / SPE-SPA (1:1). DETAILED DESCRIPTION
[0014] The present invention will be further described below in conjunction with the accompanying drawings: like Figure 1 and 2 As shown, a method for preparing a porous PTFE-filled composite membrane is described. The method functionalizes a commercial PTFE base membrane by an "ethanol + polydopamine" coupling process, and efficiently fills a high-sulfonation-degree SPEEK75 and a low-sulfonation-degree SPAES45 copolymer inside the base membrane through gravity and capillary effects. The specific steps are as follows: Step 1, functionalizing the PTFE porous substrate: The PTFE porous membrane was immersed in an ethanol solution and ultrasonically cleaned for more than 0.5 h, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; a dopamine aqueous solution of a certain concentration was prepared with dopamine hydrochloride and Tris solution (pH=8.5), the PTFE porous membrane was taken out from the ethanol solution and immersed in the above solution, and after standing for a period of time in a dark environment, it was taken out, rinsed repeatedly with deionized water, and then placed in a 60°C oven to dry for 3 h for storage.
[0015] Step 2, preparation of two-component filled polymer: A certain amount of SPEEK75 and SPAES45 were weighed and dissolved in the DMAc solution, and stirred continuously for 24 hours with a magnetic stirrer to allow the polymer to be fully dissolved, thereby preparing mixed solutions with different mass volume ratios.
[0016] Step 3: Preparation of two-component filled composite membrane: Always keep the PTFE membrane in an ethanol-wetted state, pour the pre-prepared two-component solution on the PTFE microporous membrane, apply it evenly with a film scraper, and then heat it in a film casting oven to form a film (stay at 60°C for 4-6 h, stay at 80°C for 8-10 h, stay at 100°C for 2-4 h); finally, soak the filled composite membrane in 1 mol / L HCl solution for 48 h to convert it into a proton form, then rinse with deionized water, dry it naturally and store it for later use.
[0017] The concentration of the dopamine aqueous solution in step 1 is 1.0-2.0 mg / mL.
[0018] The PTFE porous membrane in step 1 is allowed to stand in a dark environment for 10 to 18 hours.
[0019] The mass volume ratio of the two-component polymer to the DMAc solution in step 2 is 8% to 12%.
[0020] The mass ratio of SPEEK75 to SPAES45 in the two-component solution in step 3 is 0.5-2.0.
[0021] Preparation of sulfonated polyetheretherketone (SPEEK75) Slowly pour 76 mL of concentrated H2SO4 into a 250 mL pear-shaped bottle, then slowly add 4 g of PEEK powder several times, and keep stirring. After the PEEK powder is completely dissolved, heat the water bath to 50°C and react for 7-8 hours. After cooling the liquid obtained by the reaction to room temperature, pour it into deionized water to obtain a white precipitate, then wash the precipitate to neutrality and dry it in an oven at 60°C to obtain a SPEEK polymer. According to the IEC value of acid-base titration, the sulfonation degree of the prepared SPEEK is calculated to be 75%, recorded as SPEEK75.
[0022] Preparation of sulfonated poly(arylethersulfone) (SPAES45) In a three-necked flask equipped with a magnetic stirrer, an oil-water separator, a nitrogen gas guide and a condenser, 0.699 g (2.75 mmol) of 4,4'-difluorodiphenyl sulfone (DFDPS), 1.031 g (2.25 mmol) of 3,3'-disulfonated-4,4'-difluorodiphenyl sulfone (SDFDPS), 0.526 g (1.5 mmol) of bisphenol fluorene (BHPF), 0.652 g (3.5 mmol) of 4,4'-biphenyl diphenol (BP) and 15 mL of N,N'-dimethylacetamide (DMAc) were slowly added. After the solid was completely dissolved, 0.795 g (5.75 mmol) of anhydrous K2CO3 as a reaction catalyst and 15 mL of anhydrous toluene as a dehydrating agent were added. The mixture was then slowly heated to 140°C and maintained at this temperature for 4 h, and then raised to 165°C and maintained at this temperature for 6-8 h until the reaction solution became viscous. The viscous liquid was cooled to room temperature and slowly poured into deionized water to obtain a white fibrous solid precipitate, which was repeatedly washed until neutral and dried at 80°C for 12 h. The product was a SPAES polymer with a sulfonation degree of 45%, recorded as SPAES45. Example 1
[0023] Preparation of PTFE-filled composite membrane (I) Step 1, functionalizing the PTFE porous substrate: The PTFE porous membrane was immersed in an ethanol solution and ultrasonically cleaned for more than 0.5 h, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; a dopamine aqueous solution with a concentration of 1.0 mg / mL was prepared with dopamine hydrochloride and Tris solution (pH=8.5), the PTFE porous membrane was taken out from the ethanol solution and immersed in the above solution, and after standing in a dark environment for 10 h, it was taken out, rinsed repeatedly with deionized water, and then placed in a 60°C oven to dry for 3 h for storage.
[0024] Step 2, preparation of two-component filled polymer: SPEEK75 and SPAES45 polymers in a mass ratio of 2:1 were weighed and dissolved in a DMAc solution, and stirred continuously for 24 h with a magnetic stirrer to allow the polymers to be fully dissolved, thereby preparing a mixed solution with a mass volume ratio of 8%.
[0025] Step 3: Preparation of two-component filled composite membrane: The PTFE membrane was always kept in an ethanol-wetted state, and the pre-prepared two-component solution was poured onto the PTFE microporous membrane, and evenly coated with a film scraper, and then heated in a film casting oven to form a film (stayed at 60°C for 4 h, 80°C for 8 h, and 100°C for 4 h); finally, the filled composite membrane was immersed in a 1 mol / L HCl solution for 48 h to convert it into a proton form, and then rinsed with deionized water, dried naturally and stored for later use. The obtained filled composite membrane was recorded as PD@PTFE / SPE-SPA (2:1).
[0026] The performance of the prepared filled composite membrane was tested: at 30-80°C, the water absorption rate of the composite membrane PD@PTFE / SPE-SPA (2:1) was 31.2%-76.8%, the area swelling rate was 28.5%-44.6%, and the proton conductivity was 110.2-245.3 mS / cm. After Fenton oxidation treatment for 1 h (Fenton reagent: 3 wt% H2O2+2 mg / L Fe 2+ ), the mass loss of the filled film is 15.6%. Example 2
[0027] Preparation of PTFE-filled composite membrane (II) Step 1, functionalizing the PTFE porous substrate: The PTFE porous membrane was immersed in an ethanol solution and ultrasonically cleaned for more than 0.5 h, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; a dopamine aqueous solution with a concentration of 1.5 mg / mL was prepared with dopamine hydrochloride and Tris solution (pH=8.5), the PTFE porous membrane was taken out from the ethanol solution and immersed in the above solution, and after standing in a dark environment for 14 h, it was taken out, rinsed repeatedly with deionized water, and then placed in a 60°C oven to dry for 3 h for storage.
[0028] Step 2, preparation of two-component filled polymer: SPEEK75 and SPAES45 polymers in a mass ratio of 1:1 were weighed and dissolved in a DMAc solution, and stirred continuously for 24 h with a magnetic stirrer to allow the polymers to be fully dissolved, thereby preparing a mixed solution with a mass volume ratio of 10%.
[0029] Step 3: Preparation of two-component filled composite membrane: The PTFE membrane was always kept in an ethanol-wetted state, and the pre-prepared two-component solution was poured onto the PTFE microporous membrane, and evenly coated with a film scraper, and then heated in a film casting oven to form a film (stayed at 60°C for 5 hours, 80°C for 9 hours, and 100°C for 3 hours); finally, the filled composite membrane was immersed in a 1 mol / L HCl solution for 48 hours to convert it into a proton form, and then rinsed with deionized water, dried naturally and stored for later use. The obtained filled composite membrane was recorded as PD@PTFE / SPE-SPA (1:1). Figure 1 (A1) and (A2) are SEM surface images and cross-sectional images of the base membrane PTFE; Figure 1 (B1) and (B2) are SEM surface images and cross-sectional images of the filled membrane PD@PTFE / SPE-SPA (1:1); Figure 2 Includes infrared spectra of PTFE, SPEEK75, SPAES45 and PD@PTFE / SPE-SPA (1:1).
[0030] The performance of the prepared composite membrane was tested: at 30-80°C, the water absorption rate of the composite membrane PD@PTFE / SPE-SPA (1:1) was 28.4%-70.3%, the area swelling rate was 17.1%-29.3%, and the proton conductivity was as high as 80.0-260.9 mS / cm. After Fenton oxidation treatment for 1 h (Fenton reagent: 3 wt% H2O2+2 mg / L Fe 2+ ), the mass loss of the filled film is only 3.5%. Example 3
[0031] Preparation of PTFE-filled composite membrane (III) Step 1, functionalizing the PTFE porous substrate: The PTFE porous membrane was immersed in an ethanol solution and ultrasonically cleaned for more than 0.5 h, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; a dopamine aqueous solution with a concentration of 2.0 mg / mL was prepared with dopamine hydrochloride and Tris solution (pH=8.5), the PTFE porous membrane was taken out from the ethanol solution and immersed in the above solution, and after standing in a dark environment for 18 h, it was taken out, rinsed repeatedly with deionized water, and then placed in a 60°C oven to dry for 3 h for storage.
[0032] Step 2, preparation of two-component filled polymer: SPEEK75 and SPAES45 polymers in a mass ratio of 1:2 were weighed and dissolved in a DMAc solution, and stirred continuously for 24 h with a magnetic stirrer to allow the polymers to be fully dissolved, thereby preparing a mixed solution with a mass volume ratio of 12%.
[0033] Step 3: Preparation of two-component filled composite membrane: The PTFE membrane was always kept in an ethanol-wetted state, and the pre-prepared two-component solution was poured onto the PTFE microporous membrane, and evenly coated with a film scraper, and then heated in a film casting oven to form a film (60°C for 6 h, 80°C for 10 h, and 100°C for 2 h); finally, the filled composite membrane was immersed in a 1 mol / L HCl solution for 48 h to convert it into a proton form, and then rinsed with deionized water, dried naturally and stored for later use. The obtained filled composite membrane was recorded as PD@PTFE / SPE-SPA (1:2).
[0034] The performance of the prepared composite membrane was tested: at 30-80°C, the water absorption rate of the composite membrane PD@PTFE / SPE-SPA (1:2) was 21.3%-61.5%, the area swelling rate was 14.8%-25.6%, and the proton conductivity was 68.5-191.5 mS / cm. After Fenton oxidation treatment for 1 h (Fenton reagent: 3 wt% H2O2+2 mg / L Fe 2+ ), the mass loss of the filled film is only 3.0%.
[0035] Comparative Example 1 Preparation of membrane PD@PTFE / SPEEK filled with only SPEEK75, or membrane PD@PTFE / SPAES filled with SPAES45: The preparation method is the same as that in Example 2, except that in step 2, the two-component filling polymer is replaced with a single-component polymer.
[0036] Comparative Example 2 Preparation of ET@PTFE / SPE-SPA (1:1) with ethanol-modified PTFE base membrane only: The preparation method is the same as that in Example 2, except that in step 1, the "ethanol + polydopamine" coupling process modification is changed to ethanol treatment modification only.
[0037] Table 1 Basic properties of porous PTFE-filled composite membranes
[0038] Table 1 shows the basic properties of porous PTFE-filled composite membranes. As the temperature increases, the water absorption, swelling rate and proton conductivity of the membranes all increase. The proton conductivity of the PD@PTFE / SPEEK membrane in Comparative Example 1 shows a downward trend, and its antioxidant capacity is poor, with a mass loss of up to 35.8%. This is because the SPEEK polymer filled alone is prone to hydrolysis at high temperatures; although the antioxidant capacity of the PD@PTFE / SPAES membrane is good, its ability to improve proton conductivity is relatively limited; the proton conductivity of the ET@PTFE / SPE-SPA membrane with only ethanol-modified PTFE base membrane is low, and its antioxidant capacity is also poor. The proton conductivity and antioxidant stability of the PD@PTFE / SPE-SPA membrane modified by the "ethanol + polydopamine" coupling process of the PTFE-based membrane have been significantly improved. Among them, the proton conductivity of the PD@PTFE / SPE-SPA (1:1) membrane is as high as 80.0~260.9 mS / cm at 30~80℃, and the mass loss of the membrane is only 3.5%.
[0039] The above are all preferred embodiments of the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, various equivalent modifications to the present invention belong to the protection scope of the claims attached to this application.
Claims
1. A method for preparing a porous PTFE-filled composite membrane, characterized in that: The method is as follows: Step (1): Functionalization of PTFE porous substrate: The PTFE porous membrane is immersed in an ethanol solution for ultrasonic cleaning, and then immersed in a new ethanol solution to obtain the effect of membrane surface activation; dopamine hydrochloride and Tris solution are used to prepare a dopamine aqueous solution, the PTFE porous membrane is taken out from the ethanol solution and immersed in the above dopamine aqueous solution, and then taken out after standing in a dark environment, repeatedly rinsed with deionized water, and then dried for use; Step (2): Preparation of two-component filled polymer: A certain amount of SPEEK75 and SPAES45 were weighed and dissolved in the DMAc solution, and stirred with a magnetic stirrer to allow the polymer to be fully dissolved, and mixed solutions with different mass volume ratios were prepared; Step (3): Preparation of two-component filled composite membrane: The PTFE membrane is always kept in an ethanol-wetted state, and the two-component mixed solution prepared in step (2) is poured onto the PTFE microporous membrane, and evenly coated with a film scraper, and then heated in a film casting oven to form a film; finally, the filled composite membrane is immersed in a 1 mol / L HCl solution for 48 h to convert it into a proton form, and then rinsed with deionized water, and naturally dried to obtain a porous PTFE-filled composite membrane with high proton conductivity and stability.
2. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: In the step (1), the ultrasonic cleaning is performed for more than 0.5 h, the pH of the Tris solution is 8.5, the standing time in a dark environment is 10 to 18 h, and the concentration of the dopamine aqueous solution is 1.0 to 2.0 mg / mL.
3. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: The product prepared in step (1) is placed in a 60° C. oven and dried for 3 h for later use.
4. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: In the step (2), the stirring time of the magnetic stirrer is 24 h, and the mass volume ratio of the two-component polymer to the DMAc solution is 8% to 12%.
5. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: The mass ratio of SPEEK75 to SPAES45 in the two-component mixed solution in step (3) is 0.5-2.
0.
6. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: The conditions for heating the film in the film casting oven in step (3) are: staying at 60°C for 4 to 6 hours, staying at 80°C for 8 to 10 hours, and staying at 100°C for 2 to 4 hours.
7. The method for preparing a porous PTFE-filled composite membrane according to claim 1, characterized in that: The proton conductivity of the porous PTFE-filled composite membrane is as high as 80.0~260.9 mS / cm at 30~80℃, and the mass loss of the membrane is only 3.5% after Fenton treatment.
Citation Information
Patent Citations
Preparation method of composite filled electrolyte membrane
CN114464854B
Cited By
Composite proton exchange membrane for all-vanadium redox flow battery as well as preparation method and application of composite proton exchange membrane
CN120895691A